Differences in smokers' awareness of the health risks of smoking before and after introducing pictorial tobacco health warnings: findings from the 2012-2017 international tobacco control (ITC) Netherlands surveys - Dirk-Jan A. van Mourik; Gera E. Nagelhout; Marc C. Willemsen; Bas van den Putte; Hein de Vries (BMC, 2020)
Abstract Background As of May 2016, pictorial health warnings (PHWs) showing the harms of smoking were implemented in the European Union. After one year they had to be fully implemented. We studied changes in awareness of the health risks of smoking after implementation of PHWs among smokers from the Netherlands, whether the trend before the implementation changed after the implementation, and whether there were differences between subgroups. Methods We used survey data from six yearly waves of the International Tobacco Control (ITC) Netherlands Survey from 2012 to 2017. The number of participating smokers ranged between 1236 and 1604 per wave. Data were analyzed using Generalized Estimating Equations (GEE) analyses. Results Indicators of awareness of the health risks of smoking that did not change between 2015 and 2017 were perceived susceptibility (β = 0.043, p = 0.059) and perceived severity (β = − 0.006, p = 0.679) regarding lung problems. Perceived susceptibility, however, was more pronounced between 2015 and 2017 than between 2012 and 2015(p value of interaction: p = 0.044). Noticing information about the dangers of smoking (β = 0.119, p < 0.001) and knowledge about the health risks of smoking (β = 0.184, p < 0.001) increased between 2015 and 2017. These increases were both more pronounced when compared to 2012-2015 (p values of interactions: p = 0.002 and p < 0.001 respectively). Compared to high educated smokers, low educated smokers (β = − 1.137, p < 0.001) and moderate educated smokers (β = − 0.894, p < 0.001) were less knowledgeable about the health risks of smoking in 2016 and 2017. Conclusions Introducing PHWs coincided with an increase in smokers' knowledge about the health risks of smoking. Dutch tobacco control policy and campaigns should focus on improving Dutch smokers' awareness of the health risks of smoking even more, especially among low educated smokers.